Given,
"p^2 -2xyp+4y^2=0" Now, solve the quadratic equation in p, thus we get,
"p=\\frac{2xy\\pm \\sqrt{4x^2y^2-16y^2}}{2}\\\\\n\\implies p=y(x\\pm\\sqrt{x^2-4})" Hence,
"\\frac{dy}{dx}=y(x\\pm\\sqrt{x^2-4})\\\\\n\\implies \n\\frac{dy}{y}=(x\\pm\\sqrt{x^2-4})dx\\\\\n\\implies \\int \\frac{dy}{y}=\\int(x\\pm\\sqrt{x^2-4})dx\\\\\n\\implies \\ln y=\\int xdx\\pm\\int \\sqrt{x^2-4})dx\\\\\n\\implies \\ln y=\\frac{x^2}{2}\\pm \\int\\sqrt{x^2-4})dx" Since,
we know from standard integral that
Thus,
"\\int \\sqrt{x^2-4}dx=\\dfrac{x\\sqrt{x^2-4}}{2}-2\\ln\\left(\\left|\\sqrt{x^2-4}+x\\right|\\right)+C" Hence,
"\\ln y=\\frac{x^2}{2}\\pm \\dfrac{x\\sqrt{x^2-4}}{2}-2\\ln\\left(\\left|\\sqrt{x^2-4}+x\\right|\\right)+C\\\\\n\\implies y=e^{\\frac{x^2}{2}\\pm \\dfrac{x\\sqrt{x^2-4}}{2}-2\\ln\\left(\\left|\\sqrt{x^2-4}+x\\right|\\right)+C}\\\\\n\\implies y=C_1e^{\\frac{x^2}{2}\\pm \\dfrac{x\\sqrt{x^2-4}}{2}-2\\ln\\left(\\left|\\sqrt{x^2-4}+x\\right|\\right)}"
Comments
Leave a comment